2016
DOI: 10.1007/s12664-016-0619-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasonography in pediatric patients—Experience from a tertiary care center in India

Abstract: EUS is feasible and safe in children. It provides valuable information that helps in their clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Impact of EUS in pediatric patients in various studies is shown in Table 3. [3][4][5][6][7][8][9] Impact on patient management ranges from 35.5% to 98% in various studies.…”
Section: Indicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Impact of EUS in pediatric patients in various studies is shown in Table 3. [3][4][5][6][7][8][9] Impact on patient management ranges from 35.5% to 98% in various studies.…”
Section: Indicationsmentioning
confidence: 99%
“…The study showed a positive impact of EUS in 51 of 52 procedures. A recently published retrospective study from India reemphasized the safety and efficacy of EUS in children; [9] 123 diagnostic and 2 therapeutic EUS procedures were performed in 121 children. The most common indication was pancreaticobiliary (118 procedures in 114 children) followed by mediastinum (n = 5) and stomach (n = 2).…”
Section: Pancreaticobiliary Disordersmentioning
confidence: 99%
See 3 more Smart Citations